Haematological Disturbances in Dengue Haemorrhagic Fever - its Pathogenesis and Management Perspectives - H Sellahewa, Kolitha (Journal of Hematology and Oncology Research, 2015)
Haemorrhage is common to both dengue fever (DF) and dengue haemorrhagic fever (DHF). Thrombocytopaenia is exceedingly common, while prolonged partial thromboplastin time and reduced fibrinogen concentration are the other abnormal haemostatic indices evident from early in the disease course. These haematological abnormalities correlate better with the timing and severity of plasma leakage rather than the clinical haemorrhagic manifestations. Blood products including prophylactic platelet transfusions are hardly required in the management of DHF. Judicious fluid therapy is the most effective intervention to prevent complications and bleeding in DHF. Concealed haemorrhage is an important complication requiring early recognition and blood transfusions to improve outcomes. Understanding the pathogenesis of coagulopathy and the significance of altered haemostatic indices, and its co-relation to disease severity and phase of DHF, is essential for appropriate interventions particularly when DHF co-exists in patients on mandatory anticoagulation for prosthetic heart valves and atrial fibrillation.
Keywords: Dengue haemorrhagic fever; haematological disturbances; management.